EXTRACTION OF NATURAL DYES FROM CLITORIA TERNATEA FLOWER - Taif, Basitah; Mohd Som, Siti Hernida; Mohd Yusof, Ummi Zinnirah (MATTER: International Journal of Science and Technology, 2017)
This study was to extract the dye from the dried flower of Clitoria Ternatea or Blue Pea. The traditional boiling method was applied to extract its natural color. The established natural color has been studied its dyeing ability on silk fabric samples by using pre-mordanting, simultaneous mordanting, post-mordanting and dyeing procedures. The effect on fabric samples was analyzed their color characteristics through CIE L* a* b* coordinates and color fastness to washing. The test results showed that all fabrics samples produced a different range of colors where the most brilliant colors were registered with the pre-mordanting method. However, all the fabric samples were poor fastness to washing. Thus, having a different method of fixing and dyeing procedures with similar extract and concentration allowed variations of hues and shades of the silk samples.